2013
DOI: 10.5489/cuaj.1625
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in women with pelvic floor disorders

Abstract: Pelvic floor disorders (PFDs) can impact sexual function. This summary provides an overview of the impact of stress urinary incontinence and pelvic organ prolapse and their treatments on sexual function. In general, interventions that successfully address PFDs will generally improve sexual function as well. However, there are patients whose sexual function will remain unchanged despite treatment, and a small but significant minority who will report worsened sexual function following treatment for their pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
(13 reference statements)
1
18
0
Order By: Relevance
“…Rogers highlighted the importance of providing women with reassurance and evidence that POP does not prevent sexual activity. 18 Comparison of SA and NSA women in the present study revealed that NSA women exhibited greater severity of POP, with 123 (81.5%) exhibiting POP stage ! II.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Rogers highlighted the importance of providing women with reassurance and evidence that POP does not prevent sexual activity. 18 Comparison of SA and NSA women in the present study revealed that NSA women exhibited greater severity of POP, with 123 (81.5%) exhibiting POP stage ! II.…”
Section: Discussionmentioning
confidence: 52%
“…The diagnosis of UI type was based on clinical complaints, according to the standardization developed by the ICS. The condition was then classified according to the International Consultation on Incontinence Questionnaire -Short Form (ICIQ-SF) total score, as slight (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18) or very severe (19)(20)(21). 11,12 Perineal sensitivity and anal reflex were tested to investigate the integrity of the motor component of the pudendal nerve: bulbocavernosus cough and anocutaneous reflexes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found a relationship between sexual functioning and urinary incontinence due to an overactive bladder (OAB) in both men and women [4,5]. Although the specific mechanism underlying the association between OAB and sexual disorders is not fully understood, treatment of OAB is known to improve patients' sexual life [6]. Besides anticholinergic medication, intravesical treatment with onabotulinumtoxinA (Onabot/A) represents an effective alternative therapy in patients who do not respond or cannot tolerate first-line treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, physiological pelvic floor functioning, resulting from undamaged muscular and suspensory ligament systems, plays an important role in sexual satisfaction. An association between pelvic floor dysfunctionssuch as urinary stress incontinence, cystocele, rectocele, and genital prolapse in generaland female sexual dysfunctions has been observed (2). Moreover, female sexual functioning may improve after successful surgery for pelvic floor dysfunctions.…”
Section: Sirmentioning
confidence: 99%